2006
DOI: 10.1200/jco.2005.03.3225
|View full text |Cite
|
Sign up to set email alerts
|

Micrometastases in Sentinel Lymph Node in a Multicentric Study: Predictive Factors of Nonsentinel Lymph Node Involvement—Groupe Des Chirurgiens De La Federation Des Centres De Lutte Contre Le Cancer

Abstract: This study confirms the value of serial sections and the vital role played by IHC in screening for small micrometastases. Omission of additional ALND may be envisaged with minimal risk for pT1a and pT1b tumors, and pT1a-b-c tumors corresponding to tubular, colloidal, or medullar cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
15

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 64 publications
4
51
1
15
Order By: Relevance
“…Previously, clinical predictors found to display risk for NSN involvement include: age, menopausal status, primary tumor size, grade, number of SNs, number of positive lymph nodes, size of SN metastases, lymphovascular invasion and identification by H&E or IHC staining [17,25,26,27,28,29]. In our study the number of SNs removed during the SN procedure was a significant predictor of positive NSN status.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Previously, clinical predictors found to display risk for NSN involvement include: age, menopausal status, primary tumor size, grade, number of SNs, number of positive lymph nodes, size of SN metastases, lymphovascular invasion and identification by H&E or IHC staining [17,25,26,27,28,29]. In our study the number of SNs removed during the SN procedure was a significant predictor of positive NSN status.…”
Section: Discussionmentioning
confidence: 61%
“…The risk of harboring additional NSN metastases if the SN is afflicted with micrometastatic disease (pN1mi) reportedly ranges from 13.4 to 26% [17,18,19,20]. Cserni and colleagues estimated the risk to hover between 10% and 15% for micrometastases and isolated tumor cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, within those with SLN MM no subgroup of tumour size or grade could be identified that did not have non-SLN involvement. Interestingly, Houvenaeghel et al [50] found that the method employed for MM detection was a significant predictive factor for non-SLN involvement. Furthermore, Tommaso et al [51] demonstrated that the anatomical location of MM within the SLN was an independent predictor of non-SLN involvement, with intranodal lesions being more strongly associated with non-SLN metastasis than sinusal lesions.…”
Section: Analysis Of the Sentinel Lymph Nodementioning
confidence: 99%
“…Cserni et al [40,41] found SLN ITC to be associated with a non-SLN metastatic rate of 8.5-13.5%. The French multicentre study reported relatively high rates (16%) of non-SLN metastases associated with SLN ITC, without a statistically significant difference between ITC and MM for predicting non-SLN positivity (16% vs. 14.3%) [55]. Interestingly, the detection method was a significant predictor of non-SLN involvement.…”
Section: Evidence In Favourmentioning
confidence: 94%